2012
DOI: 10.1007/s10008-012-1892-3
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical performance of strontium-doped neodymium nickelate mixed ionic–electronic conductor for intermediate temperature solid oxide fuel cells

Abstract: The Nd 2− x Sr x NiO 4+δ (x00.1-0.5) solid solutions prepared by combustion synthesis are of submicron/superfine crystallite size. The crystal structure estimated by Rietveld analysis reveals increase in space in the rock salt layer on partial replacement of Nd 3+ by Sr 2+ . The transition from negative temperature coefficient to positive temperature coefficient of conductivity is observed at 913 K. The maximum dc conductivity (σ01.3±0.02 Scm −1 at 973 K) is obtained for x00.2 in Nd 2− x Sr x NiO 4+δ . The low… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 41 publications
0
11
0
1
Order By: Relevance
“…La n + 1 Ni n O 3n + 1 has been prepared in the n = 1, 2, and 3 phases [15,16], and even in combination as a functionally graded cathode that combines the high surface exchange of the n = 1 phase with the superior electronic conductivity of the n = 3 phase [17], representing the current best-in-class cathode for La n + 1 Ni n O 3n + 1 with a polarization resistance of 1.06 Ω • cm 2 at 650°C. Nd n + 1 Ni n O 3n + 1 has proven to be reactive with some common electrolytes and has moderate oxygen transport coefficients compared with other rare earth nickelates [18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…La n + 1 Ni n O 3n + 1 has been prepared in the n = 1, 2, and 3 phases [15,16], and even in combination as a functionally graded cathode that combines the high surface exchange of the n = 1 phase with the superior electronic conductivity of the n = 3 phase [17], representing the current best-in-class cathode for La n + 1 Ni n O 3n + 1 with a polarization resistance of 1.06 Ω • cm 2 at 650°C. Nd n + 1 Ni n O 3n + 1 has proven to be reactive with some common electrolytes and has moderate oxygen transport coefficients compared with other rare earth nickelates [18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…Although a number of studies have been reported to clarify the mechanism of oxygen reduction reaction on RuddlesdenePopper type Ln 2 NiO 4þd (Ln ¼ La, Pr, Nd) cathodes [49,55,75e80], the interpretation of the impedance response is not straightforward and still non-conclusive. Based on the literature, the impedance arcs of Ln 2 NiO 4þd (Ln ¼ La, Pr, Nd) cathodes could be ascribed to a number of elementary reaction processes including ion transfer at the cathode-electrolyte interface [55,79], surface exchange [80], oxygen atomic diffusion [49], charge transfer reaction [77,79], oxygen adsorption/dissociation [78] and gas-phase diffusion [78]. We have performed a systematic analysis on the impedance spectra of the LNOeGDC composite cathode; based on temperature-and pO 2 -dependencies of the individual arcs, the rate limiting processes were identified as the cathode-electrolyte interfacial process and the surface exchange for high-frequency impedance and gas-phase diffusion for low-frequency impedance.…”
Section: Resultsmentioning
confidence: 99%
“…Remarkable improved electrochemical performance due to the partial substitution of Sr in Nd 0.8 Sr 1.2 CoO 4Àd has been demonstrated [20]. Lowest electrode polarization resistance (R p ¼ 0.52 ± 0.015 U cm 2 at 700 C) has been reported for Nd 2Àx Sr x NiO 4Àd when x ¼ 0.2 [21].…”
Section: Introductionmentioning
confidence: 94%
“…Further, CeO 2 is abundant in the Earth's crust. It has thermo-chemical stability against Nd 1.8 Sr 0.2 NiO 4Àd [21].…”
Section: Introductionmentioning
confidence: 99%